2007
DOI: 10.1136/pgmj.2007.061267
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effects of Tai Chi Chuan and Chi Kung training in patients with symptomatic heart failure: a randomised controlled pilot study

Abstract: Objective: To study the effect of Tai Chi on exercise tolerance in patients with moderate heart failure. Design: Randomised parallel group study balanced for baseline variables. Setting: Cardiology Department, Royal Hallamshire Hospital. Patients and methods: 52 patients (42 men, mean age (68.9 years), range (46-90 years), and 10 women, mean age (70.0 years), range (58-82)) with chronic heart failure (New York Heart Association symptom class II-III) were studied. Patients were randomised to Tai Chi Chuan twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
138
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(139 citation statements)
references
References 20 publications
(19 reference statements)
0
138
1
Order By: Relevance
“…Other studies used symptoms as an indicator of OA severity, such as pain intensity on a visual analogue scale (VAS), and scored 4.4 of the 10 points36 and 48.6 of the 100 points 54. Four of the five HF studies22 43 52 55 used the New York Heart Association (NYHA) classification for HF and stated that the participants were in classes I–III, indicative of mild-to-moderate HF severity. Three of the five COPD studies40 42 56 reported forced expiratory volume in 1 s (FEV 1 ) indicative of participants with moderate-to-severe COPD and two studies reported stages of severity 35 57…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies used symptoms as an indicator of OA severity, such as pain intensity on a visual analogue scale (VAS), and scored 4.4 of the 10 points36 and 48.6 of the 100 points 54. Four of the five HF studies22 43 52 55 used the New York Heart Association (NYHA) classification for HF and stated that the participants were in classes I–III, indicative of mild-to-moderate HF severity. Three of the five COPD studies40 42 56 reported forced expiratory volume in 1 s (FEV 1 ) indicative of participants with moderate-to-severe COPD and two studies reported stages of severity 35 57…”
Section: Resultsmentioning
confidence: 99%
“…Sun style Tai Chi was used in four OA studies23 33 37 38 and two COPD studies 56 57. Wu style Tai Chi was taught in only two studies (1 OA54 and 1 HF22). The type of Tai Chi was not stated in six studies 24 34 39 40 45 53.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…37,43,44,51 Three studies were weak in quality. 37,43,44 Two studies that reported the percentages willing to participate indicated that large numbers of persons refused, although no reasons were given. 43,51 Although the findings are promising (d range, .4 to 1.6), the overall body of evidence is weak.…”
Section: Complementary and Alternative Medicinementioning
confidence: 98%